2022
DOI: 10.17478/jegys.1153098
|View full text |Cite
|
Sign up to set email alerts
|

Gifted students' value perceptions: differentiation to socio-demographic variables

Abstract: Science and Art Centers (BİLSEM) operate within the body of the Ministry of National Education (MEB) in Turkey in order to develop individual talents and raise awareness of gifted students in preschool, primary school, secondary school and high school in a way that does not disrupt their education at schools. Identifying gifted students at an early age and educating them in line with their abilities is of great importance not only for the individual happiness of these children, but also for the society. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…al. 2017;Pekdoğan and Bozgün 2017;Dede and Uzun 2020;Ünal and Benzer 2021;Naycı 2021;Cavlak et al 2021;Doğan et al 2022;Uzun et al 2022), while it has been observed that postgraduate theses are also examined in other fields (Tutcu and Talaş 2021;Temel et al 2016;Altaş and Acar 2018;Tezer et al 2019;Korkmaz and Çetinkaya 2019;Göncü Serhatlıoğlu and Dolgun 2019;Karaman et al 2020;Alkar and Atasoy 2020;Ilkım et al 2021). Although many different methods are used to examine the content of the studies, the content analysis method, which has been applied in many fields in recent years, has come to the fore (Cleave et al 2017;López-Bonilla et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…al. 2017;Pekdoğan and Bozgün 2017;Dede and Uzun 2020;Ünal and Benzer 2021;Naycı 2021;Cavlak et al 2021;Doğan et al 2022;Uzun et al 2022), while it has been observed that postgraduate theses are also examined in other fields (Tutcu and Talaş 2021;Temel et al 2016;Altaş and Acar 2018;Tezer et al 2019;Korkmaz and Çetinkaya 2019;Göncü Serhatlıoğlu and Dolgun 2019;Karaman et al 2020;Alkar and Atasoy 2020;Ilkım et al 2021). Although many different methods are used to examine the content of the studies, the content analysis method, which has been applied in many fields in recent years, has come to the fore (Cleave et al 2017;López-Bonilla et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Every society wants to develop in the fields of science and art, to become stronger in the field of industry, and to improve the quality of life of its individuals, and believes that the way to realize all these is through the education of gifted individuals. (Küçük, Gökdere & Çepni, 2005;Choi, 2009;Pekdoğan & Bozgün, 2017;Han & Shim, 2019). In the Marland Report published in 1972, it was stated that the education system at the time was not adequate for the talent development of gifted individuals (Marland, 1972).…”
Section: Introductionmentioning
confidence: 99%